Pengembangan Bahan Ajar Multimodal Berbasis Android dalam Meningkatkan Kemampuan Numerasi Siswa pada Materi Rasio di Kelas VI UPTD SD Inpres Naikoten 2 - Maria Septima Manek; Damianus Dao Samo; Vera Rosalina Bulu (Lembaga Yasin AlSys, 2025)
Based on interviews and needs analysis conducted at UPTD SD Inpres Naikoten 2, Kupang City, ratio material was identified as one of the topics most difficult for sixth-grade students to understand. The use of conventional printed textbooks has led to low learning enthusiasm and weak numeracy skills among students. This study aims to develop an Android-based multimodal teaching material that is valid, practical, and effective in improving students’ numeracy skills in learning ratios. The research employed a development method using the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. Data collection instruments included observation, interviews, questionnaires, and learning outcome tests, with data analyzed using descriptive percentages and qualitative analysis. Validation results showed feasibility scores of 90.6% from design experts and 85.6% from subject matter experts. Student responses to the teaching material reached 84% in the small group and 84.25% in the large group, while the mathematics teacher's response was 80.4%. Product effectiveness was indicated by an N-Gain score of 0.75 (high category) in the small group and 0.58 (moderate category) in the large group. The study concludes that Android-based multimodal teaching material is highly feasible, practical, and effective for teaching ratio concepts in mathematics, and contributes significantly to improving elementary students' numeracy skills.